Risk and Return of Retail Sukuk and Retail Bond in Indonesia Period 2008-2017 (Comparative Study) - Rahma Yudi Astuti; Asad Arsya Brilliant Fani (AKSES: Jurnal Ekonomi dan Bisnis, 2020)
Sukuk and Bonds has differences and similarities. Fundamental differences between sukuk and bonds are first, underlying asset in every sukuk issuance, concept of profit loss sharing and the use of Islamic contracts. Whereas conducted research in practice of differences between sukuk and bonds are still an on-going discussion. This study aims to add the evidence in the discussion regarding whether there is differences between sukuk and bonds in the world of practice, provide investment preferences as well as educating investors in choosing sukuk or bonds as a sustainable and smooth instrument. The method used is Mann Whitney U-Test to test whether there is a different between yield to maturity (return) and standard deviation (risk) of both instruments. Using secondary data of Retail Sukuk (SR) and Retail Bonds (ORI) period 2008-2017 obtained from Indonesia Stock Exchange, Indonesia Bond Market Directory and Indonesia Bond Pricing Agency. The result shows that there is no significance difference of retail sukuk return and risk with retail bonds in Indonesia. Besides retail bonds are show higher return than retail sukuk because of higher coupon and longest mature date. While, retail sukuk is more stable rather than bonds as it backed up by the real underlying asset. Keywords: Retail Sukuk (SR), Retail Bonds (ORI), Yield to Maturity